A prospective observational study on the clinical profile of ischemic stroke in a tertiary care centre in Thrissur, Kerala - Mary Grace N C; Shameer V K; Rajesh K R; Raju Raghavan; Sreejesh Sreejesh; Sakti Sakti (International Journal of Medical Research and Review, 2016)
Introduction: India is facing an increasing burden of diseases like coronary artery disease and stroke. Another peculiarity is that the number of cases of stroke in the young is more when compared to the west. There are also discrepancies among the different states of India regarding the epidemiological and clinical features of stroke. The aim of this study was to gather information regarding the clinical profile of patients admitted with ischemic stroke in a tertiary care centre in Thrissur, a district in the state of Kerala.Materials and Methods: The study included 100 consecutive patients admitted with the diagnosis of ischemic stroke, in the medicine wards of Government Medical College Thrissur. Patients above the age of 18 years and those cases in which the diagnosis was confirmed by CT scan of the brain were included in the study.Results: The majority of the patients were above 65 years of age (63%) and among the elderly 34 (54 %) belonged to the age group of 65-74 years. In the age group above 65 years there were more females than males. The most common risk factor for stroke was hypertension. In the age group above 65 years, majority of the females had high LDL cholesterol values (>100 mg %) p 0.02 OR 4.7 95%CI 1.38-15.9.Conclusion: Elderly females have a greater predilection for the occurrence of stroke. Hypertension is the most common risk factor for stroke. Elevated LDL cholesterol is observed more often in elderly females. Earlier interventions aimed at the risk factors may prevent the occurrence of stroke.